PENGARUH IPM, PDRB DAN JUMLAH PENGANGGURAN TERHADAP PENDUDUK MISKIN DI PROVINSI JAMBI - M Alhudhori (Universitas Batanghari Jambi, 2017)
In fact the construction economy is rangkayan activity by exploiting the whole potential of the basic capital as epektif and efficiently through perancanaan kesejahtraanin order to improve society. The fulfillment of the basic needs of the society especially health, education, food and nutrition is something very fundamental in the context of the development of community welfare (welfare), human development (humandevelopment) and reduction of poverty (poverty reduction). Strategic issues in the governance of the Jambi province are not much different from the Central Government (the problem), namely the still high number of poverty. Based on multiple linear regression analysis of the HDI have a positive relationship towards the poor population where if the HDI rose 1 percent then the number of poor population will rise of0.358. Based on multiple linear regression analysis of the GDP had a negative relationship toward the poor population, which if GDP rises 1 percent then the number ofpoor population will be down by-0.006. Multiple linear regression analysis based onthe number of unemployment has positive relationship towards the poor population where if the number of unemployed rose 1 percent then the number of poor population will rose by 0.010.Keyword: influence of IPM, PDRB and the number of unemployed